The Issue on Indo-European Diglossy: Some Aspects of Lexis and Semantics of Fire and Water in the Early Indian and Greek Poetical Texts - Veteikis, Tomas (Acta Orientalia Vilnensia, 2002)
The present paper contributes to the scientific discussion initiated in the early 20th century by H. Güntert (1921) and later carried on by J. Friedrich, C. Watkins, A Heubeck, V. N. Toporov, T. Y. Elizarenkova. and others who produced arguments on the twofold lexical and semantic structure of ancient Indo-European languages. Their thesis was based on the direct evidence of dichotomy of “Language of Gods and Language of Men” in ancient Iranian, Indian, Hittite, Greek, Irish and Celtic texts. This dichotomy or diglossy may coincide with the dichotomy of the sacred language of priests and poets, on the one hand, and the ordinary language of people, on the other. It is likely that this diglossy also embraces the twofold lexis of natural phenomena, such as “two waters”, “two fires”, “two bloods” and the like, where one of the two words is supposed to denote a thing of active kind and the other of inactive (passive) kind. The present article is aimed at the search (but not at an exhaustive one yet) for different semantic levels of terms designating fire and water in the earliest Indian and Greek texts: in Rigveda and Homeric epics and hymns. The texts under investigation share a common notion that fire and water, on the one hand, are natural elements in macro and microcosms and, on the other, they are agents of higher level which have their social and ritual role in family and religion. Yet these levels are rather intermingled and difficult to demarcate. The predominant Rigvedic terms for fire and water, which stem from the common Indo-European root of the word group denoting active things, - agniḥ and āpaḥ - designate personified or non-personified fire and water. Synonyms of these terms have no connotation of personal representation and ritual sphere, except for the synonyms which are applied to a particular god. The Greek terms for fire and water πυ̃ρ and υ̃δωρ are derivatives from the proto Indo-European stem, denoting inactive and inanimate object. Despite the fact, that ancient Greek texts produce no such term which lexically represents the opposite phenomena, i.e. active and animate fire and water (with an exception of some place-names), such meanings can be reconstructed by the analysis of the opposite epithets of Greek terms for fire and water, and also from metonymical use of divine names (Hephaistos instead of πυ̃ρ). Finally, the research leads to a conclusion that reconstruction of Indo-European diglossy should embrace not only lexical, but also semantic field of investigation. This is especially relevant to religious texts (hymns of Rigveda and partly Homeric hymns. in the present case), where different semantic levels and their lexical equivalents are traced.